Simulation Analysis of the Four Configurations of Solar Desiccant Cooling System Using Evaporative Cooling in Tropical Weather in Malaysia. (2nd February 2014) - Dezfouli, M. M. S.; Mat, S.; Pirasteh, G.; Sahari, K. S. M.; Sopian, K.; Ruslan, M. H.
Abstract : A high demand for air conditioning systems exists in hot and humid regions because of the warm climate during the year. The high energy consumption of conventional air conditioning system is the reason for our investigation of the solar desiccant cooling system as an energy-efficient cooling system. Four model configurations were considered to determine the best configuration of a solar desiccant cooling system: one-stage ventilation, one-stage recirculation, two-stage ventilation, and two-stage recirculation. These models were stimulated for 8, 760 hr of operation under hot and humid weather in Malaysia. Several parameters (i.e., coefficient of performance or COP, room temperature and humidity ratio, and the solar fraction of each system) were evaluated by detecting the temperature and humidity ratio of the different points of each configuration by TRNSYS simulation. The latent and sensible loads of the test room were 0.875 kW and 2.625 kW, respectively. By investigating the simulation results of the four systems, the ventilation modes were found to be higher than the recirculation modes in the one- and two-stage solar desiccant cooling systems. The isothermal dehumidification COP of the two-stage ventilation was higher than that of the two-stage recirculation. Hence, the two-stage ventilation mode desiccant cooling system in a hot and humid area has higher efficiency than the other configurations.